The Implementation of Scientific Approach in Teaching English at the First Grade of SMK Muhammadiyah 1 Sukoharjo: Naturalistic Study - Rizki Prihantoro, Ardika, Dr. Dwi Haryanti, M. Hum, Aryati Prasetyarini, M. Pd (2015)
This research discusses two major concerns. First is the implementation of scientific approach for teaching learning English in SMK Muhammadiyah 1 Sukoharjo. Second is the students' opinions on the approach in teaching learning English. This research aims to know the implementation of scientific approach in teaching learning English at the first grade of SMK Muhammadiyah 1 Sukoharjo. The type of this research is descriptive qualitative research. The researcher gets all the data from event, informant, and document. The methods of collecting data are observation, interview, documents. The technique of data analysis is descriptive interactive which comprises three procedures, namely: data reduction, data display, and drawing conclusion. The technique of data analysis is to answer the implementation of scientific approach and the students' opinions on the approach in teaching learning English. The result of this research shows that: 1) the implementation of scientific approach in teaching learning English at the first grade of SMK Muhammadiyah 1 Sukoharjo was complete. The teacher used project-based learning as method and the teacher used two techniques in teaching learning process discussion and presentation. There are five activities in teaching learning process, such as: observing, questioning, experimenting, associating, and networking based on the 2013 curriculum. 2) the students' opinions about the approach in teaching learning English at the first grade of SMK Muhammadiyah 1 Sukoharjo were very positive opinions. There are five categories from the result of students' opinions by students' questionnaire, such as: a) the material is easy to understand, (b) the students enjoy the English learning, (c) the teaching learning English situation is very fun, (d) the teaching learning English atmosphere is not boring, (e) the teaching learning English is very interesting. Keyword: scientific approach, teaching learning English, the 2013 curriculum.